PENGETAHUAN, SIKAP, DAN PERILAKU ORANGTUA MENGENAI PENCEGAHAN KECELAKAAN RUMAH PADA ANAK - Isfanda Isfanda; Eka Yunita Amna; Rima Pebriana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
An accident is an event that occurs unintentionally which can result in injury. Accidents are a major cause of morbidity and mortality in children. This study aims to find out the knowledge and attitudes of parents regarding the prevention of home accidents in children using analytical descriptive methods with a cross-sectional approach design. The study was conducted in March-May 2021 and obtained as many as 85 samples. Respondent characteristics were measured using a questionnaire. The results showed that 57% of parents had good knowledge, 55.30% of parents had good attitudes, 76.50% of parents had good prevention of home accident, and there were 81.20% of children who often fell. This research shows that parents have good knowledge, attitude, and prevention of home accidents in children.Keywords: trauma accidents, non-traumatic accidents, accident prevention